Kualitas Produk Dan Promosi Terhadap Minat Nasabah Untuk Meningkatkan Profitabilitas Di PT. BPR Syariah Lantabur Tebuireng Jombang - Miftakhur Rohmah; Athi’ Hidayati (edujavare, 2023)
The objective of this research is to examine how product quality and promotion influence customer interest, both individually and collectively. The approach employed is descriptive quantitative by collecting data in the form of numbers. The population in this study is ukhuwah savings customers. The sample amounted to 68 customers using incidental sampling techniques. The methodolody utillized is the analysis of multiple linear regression. The findings from this investigation show that. Product quality affects customer interest in ukhuwah savings products at PT. BPR Syariah Lantabur Tebuireng Jombang with a computed t score of 2.798 > t table 1.669 and sig value 0.007 < 0.05. Promotion affects customer interest in ukhuwah savings products at PT. BPR Syariah Lantabur Tebuireng Jombang with a calculated t value of 4.004 > t table of 1.669 and a sig value of 0.000 < 0.05. Product quality and promotions simultaneously affect customer interest in ukhuwah savings products at PT. BPR Syariah Lantabur Tebuireng Jombang with F value count 75.556 > F table 3.138 and sig value 0.000 < 0.05.